SIKAP TAWAKAL DENGAN KECEMASAN MENGHADAPI UJIAN NASIONAL PADA SISWA KELAS XII MADRASAH ALIYAH DI KOTA PALEMBANG - Bobi Januar Iskandar; Muhammad Noupal; Kiki Cahaya Setiawan (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2018)
The independent variable in this research is the attitude of tawakal. While the dependent variable is anxiety facing the national exam. Hypothesis research there is correlation between attitude tawakal with anxiety face national exam at student class XII. The samples were taken using Cluster Random Sampling technique. The sample in this study amounted to 165 students class XII IPA 1, XII IPA 2, XII IPA 4, XII IPS 1 and XII IPA 3. Methods of data retrieval in this study using the scale of attitude tawakal and the scale of anxiety face the national exam. Data analysis method used to test the research hypothesis using Pearson Product Moment analysis. All data analysis calculations were performed using the SPSS (Statistical Packager For Social Science) software version 22.00. The conclusion of this research is there is a significant negative correlation between attitude tawakal with anxiety face national examination at student of class XII (r = -0,596; p = 0,000). This suggests that the role of tawakal attitude to anxiety is very important. Humans who have a high tawakal attitude will have a low anxiety and vice versa.